The Exploration of Poor Ovarian Response–Related Risk Factors: A Potential Role of Growth Differentiation Factor 8 in Predicting Ovarian Response in IVF-ET Patient - Bai, Long; Pan, Huihui; Zhao, Yinjun; Chen, Qingqing; Xiang, Yu; Yang, Xiaohang; Zhu, Yimin (Frontiers in Endocrinology, 2021)
Controlled ovarian hyperstimulation (COH) is the most common therapeutic protocol to obtain a considerable number of oocytes in IVF-ET cycles. To date, the risk factors affecting COH outcomes remain elusive. Growth differentiation factor 8 (GDF-8), a member of transforming growth factor β (TGF-β) superfamily, has been long discerned as a crucial growth factor in folliculogenesis and the aberrant expression of GDF-8 is closely correlated with the reproductive diseases. However, less is known about the level of GDF-8 in IVF-ET patients with different ovarian response. In the present study, the potential risk factors correlated with ovarian response were explored using logistic regression analysis methods. Meanwhile, the expression changes of GDF-8 and its responsible cellular receptors in various ovarian response patients were determined. Our results showed that several factors were intensely related to poor ovarian response (POR), including aging, obesity, endometriosis, surgery history and IVF treatment, while irregular menstrual cycles and PCOS contribute to hyper ovarian response (HOR). Furthermore, POR patients exhibited a decrease in numbers of MII oocytes and available embryos, thereby manifesting a lower clinical pregnancy rate. The levels of GDF-8, ALK5 and ACVR2B in POR patients were higher compared with those in control groups whereas the expression level of ACVR2A decreased in POR patients. In addition, clinical correlation analysis results showed that the concentration of GDF-8 were negatively correlated with LH and estradiol concentration, antral follicle count. Collectively, our observations provide a novel insight of ovarian response-associated risk factors, highlighting the potential role of GDF-8 levels in ovarian response during COH process.